GAMBARAN PENERAPAN SURGERY PATIENT SAFETY FASE SIGN OUT PADA PASIEN POST OPERASI BEDAH MAYOR DI INSTALASI BEDAH SENTRAL RSUD KEBUMEN. - Hermawan, Indra; -, Saryono; Santoso, Dadi (LPPM STIKES MUHAMMADIYAH GOMBONG, 2014)
Sign out phase implementation of Surgery Patient Safety is an importantpart in the nursing services. Nurses as the main actors who haveresponsibility to provide services based on patient safety guidelines. Theaim of this study is todetermine descriptively about sign out phase implementation of Surgery PatientSafety on the major surgery postoperative patient in central surgery room (Ind:IBS) of kebumen regional hospital. This is a descriptive research usingobservational and evaluation checklist of Surgery Patient Safety. The samplesconsist of 336 respondents taken by Quotes technique. This research usingunivariate analysis. There were 100% records to the surgery procedure and name of the surgery,instrument calculation, specimen labeling that need supportive examination, andfollow up plane, and 331 actions of report of inspection and documentation ofinstrument problem. Itcan be concluded that the overview of Surgery Patient Safety in Sign Out Phaseimplementation for the major surgery postoperative patient in central surgeryroom of kebumen regional hospital is categorized good. Keywords: Major surgery, Postoperative,Surgery patient safety, the sign out phase.